Ordinary differential equations : a computational approach - Roberts, Charles E. Jr. (London, United Kingdom : Prentice-Hall, 1979)
The main purpose of this text is to present ordinary differential equations in a manner that is compatible with the way they are used in many professions.
1. Introduction -- 2. The initial value problem -- 3. First order differential equations -- 4. The initial value problem -- 5. System of first order equations: Theory -- 6. Linear differential equations -- 7. Applications of the second order linear differential equation -- 8. Power series methods -- 9. Systems of first order equations: methods of solution -- 10. Two point boundary value problems.
Includes bibliographical references and index.
Keywords: ORDINARY DIFFERENTIAL EQUATIONS